Clinical procedures for medical technology specialists - Laurence J. Street (Taylor and Francis Group, LLC, 2011)
As healthcare becomes more complex, the integration of all members of the team becomes even more important. Part of this integration requires that all team members have a grasp of the fundamentals of the medical and surgical treatments they are involved in. Written specifically for paramedical professionals who support doctors and nurses, Clinical Procedures for Medical Technology Specialists presents a clear and concise description of the more common diagnostic and treatment procedures used in current medical care